Detecção sorológica e molecular Theileria equi em equinos do Estado da Paraíba - Ribeiro, Luana Paula da Silva (2015)
Equine piroplasmosis is a tick borne infectious disease, whose etiologic agent Theileria equi is an obligatory erythrocyte parasite. Thus, the aim of this study was to evaluate the prevalence and molecular data of T. equi in horses from urban and rural areas in six cities of Paraiba state, in northeastern Brazil. Blood samples from 119 animals were collected in order to evaluate total protein values, globular volume and also performing indirect immunofluorescence assay (IFA) and polymerase chain reaction (PCR). Of all the animals studied, 61, 6% (85/119) were seropositive at IFAT and 49, 6% (59/119) were positive in PCR. In the evaluation of epidemiological surveys for analysis of risk factors, there was no significant association between the presence of ticks, age or sex with seropositivity or molecular detection of T. equi (p> 0.05). The prevalence of the infection in serological and molecular analysis when compared with hematocrit values less than 32% was 68.9% and 64.4%, respectively. The horses that had increased total plasma protein (> 7.9 g / dL) was 66, 38% in serology and 52,33% molecular analysis. Thus, it is need to control ticks, monitoring the health status of animals and preparation of active surveillance programs to prevent the spread of this parasite to susceptible animals.